The Middle School Concept Implementation Gap: A Leadership Lens - Julia G. Rheaume (Middle Grades Review, 2022)
Middle school scholars periodically lament the lack of holistic implementation of the middle school concept (Alverson et al. 2021; Dickinson & Butler, 2001; Lounsbury 2013; Schaefer et al. 2016;). The results of a case study conducted in Alberta, Canada (Rheaume, 2018) are compared to a recent examination of the current status of middle schools in America (Alverson et al., 2021) to illustrate common implementation gaps and challenges. Consideration of the role of middle level leadership in supporting the implementation of the middle school concept is followed by a proposed expansion of the developmentally responsive middle level leadership (DRMLL) model (Brown et al., 2002).
Keywords: developmentally responsive; relational leadership; middle school; middle school leadership; middle school concept